The Effect of Core Product Quality on Organizational Performance Considering the Mediating Role of Fan Satisfaction (Case study: Persepolis and Esteghlal Football Club) - Mehdi Pourhossein; Ebrahim Ali Doost Ghahfarkhi; Mehrzad Hamidi; Khadijeh Pourzabih Sarhamami (Sports Business Journal)
Purpose: Establishing an equilibrium between financial performance and sporting performance is one of the most critical concerns of current managers in professional football clubs. This study aimed to develop a model to investigate the effect of a core product quality on financial and sporting performance considering the mediating role of fan satisfaction in the two most popular clubs in Iran (Persepolis and Esteghlal).Methodology: The data was collected using the questionnaire survey and purposive and available sampling method. The statistical population of the study included all managers, experts, elites, and individuals who had sufficient knowledge and information (like club veterans) concerning the two most popular football clubs in Iran (Persepolis and Esteghlal). The data from 175 questionnaires was analyzed through the Structural Equation Modelling technique under the Partial Least Squares approach using PLS innovative software.Findings: The results demonstrated that there was a positive and significant relationship between the core product quality and organizational (financial and sporting) performance. Also, the mediating effect of fan satisfaction in the relationship between core product quality and organizational performance was confirmed.Originality: The model, provided as an effective tool, can help club managers analyze and choose the best club development strategies to equilibrate the financial and sporting performance of the club to more confidently achieve the organizational goals. The importance of these findings is that the application of appropriate mixed policies from fan satisfaction and core product quality will have a significant impact on improving organizational performance.